Improve satellite radio navigation system performances using linear Kalman filtering - Hajiyev, C. (IEEE, 2003)
A recursive Kalman filter which estimates the user coordinates has been designed, when satellite radio navigation system is used. This filter also makes finding the distance measuring errors, resulted from the time differences between user and satellite (clock bias), possible. Results of performed simulation revealed that the designed filter has worked with high accuracy and has considered both user coordinates and clock bias in real time.